ANALISIS KUALITAS PELAYANAN BARBERSHOP TERHADAP LOYALITAS PELANGGAN DI MA’HAD AL-ZAYTUN DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH Studi Pada Siswa Kelas 12 Rijal Ma’had Al-Zaytun - Abi Qisthon; Siti Ngainnur Rohmah; Ahmad Asrof Fitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the quality of service provided by barbershops in Ma'had Al Zaytun according to customer perceptions, analyze the effect of service quality on customer loyalty, and explain the relationship between service quality and customer loyalty in the perspective of Sharia Economic Law. The research applied an explanatory sequential mixed method design, in which researchers first conducted a quantitative approach by distributing questionnaires by simple random sampling to 180 12th grade Rijal students from a total population of 328, based on the Slovin formula (5% margin error). After the quantitative analysis was deemed inadequate, the qualitative phase continued in the form of in-depth interviews with managers and barberman to deepen the understanding of quantitative data. Simple linear regression statistical analysis showed that service quality contributed 89.5% to customer loyalty (R² = 0.895), with a very strong correlation of 94.6% (r = 0.946). In addition, most respondents expressed satisfaction with the aspects of cleanliness, comfort of the place, and friendliness of the barberman, although there were complaints related to the discrepancy of the cut results and the lack of professional barberman training. From the perspective of Sharia Economic Law, the service practices at Ma'had Al Zaytun Barbershop reflect the principles of trustworthiness, justice, and maslahah, but professionalism still needs to be improved as part of the service contract (Ijarah bil 'amal). The results of this study make an important contribution to the development of Islamic services that are aligned with sharia principles, oriented towards customer satisfaction, and have the potential to build sustainable loyalty. Keywords: service quality; customer loyalty; Sharia Economic Law; barbershop;